Research methods in child language a practical guide - Hoff, Erika 1951- (Guides to research methods in language and linguistics, 2012)
"This is a comprehensive and accessible guide to the methods researchers use to study child language, written by experienced scholars in the study of language development. [The book] presents a comprehensive survey of laboratory and naturalistic techniques used in the study of different domains of language, age ranges, and populations, and explains the questions addressed by each technique ; presents new research methods, such as the use of functional Near Infrared Spectroscopy (fNIRS) to study the activity of the brain ; [and] expands on more traditional research methods such as collection, transcription, and coding of speech samples that have been transformed by new hardware and software."--Publisher's website.